Identification of Potential Blind-Side Hypermelanosis-Related lncRNA–miRNA–mRNA Regulatory Network in a Flatfish Species, Chinese Tongue Sole (Cynoglossus semilaevis) - Li, Yangzhen; Hu, Yuanri; Cheng, Peng; Chen, Songlin (Frontiers in Genetics, 2022)
Blind-side hypermelanosis has emerged as a major concern in commercial rearing environments of the flatfish aquaculture industry. To date, the underlying molecular mechanisms are not well understood. To fill this gap, in this study, whole transcriptomic sequencing and analyses were performed using normal skins and hypermelanic skins of the blind side of Chinese tongue sole (Cynoglossus semilaevis). Differentially expressed long non-coding RNAs (DElncRNAs), miRNAs (DEmiRNAs), and genes (DEGs) as well as their competing endogenous RNA (ceRNA) networks were identified. Totals of 34 DElncRNAs, 226 DEmiRNAs, and 610 DEGs were identified. Finally, lncRNA-miRNA-mRNA regulatory networks (involving 29 DElncRNAs, 106 DEmiRNAs, and 162 DEGs) associated with blind-side hypermelanosis were constructed. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of 162 DEGs in ceRNA networks identified DEGs (e.g., oca2, mc1r, and ihhb) in pigmentation related biological processes and DEGs (e.g., ca4, glul, and fut9) in nitrogen metabolism, glycosphingolipid biosynthesis, and folate biosynthesis pathways, as well as their corresponding DElncRNAs and DEmiRNAs to potentially play key regulatory roles in blind-side hypermelanosis. In conclusion, this is the first study on the ceRNA regulatory network associated with blind-side hypermelanosis in flatfish. These new findings expand the spectrum of non-coding regulatory mechanisms underpinning blind-side hypermelanosis, which facilitates the further exploration of molecular regulatory mechanisms of malpigmentation in flatfish.